ANALYSIS OF THE USE OF PROJECT MANAGEMENT TOOLS BY UKRAINIAN COMPANIES - OLEKSYUK, Hanna; POPADYNETS, Nazariy; PITYULYCH, Mykhailo (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The socio-economic condition of Ukraine undergoes fundamental changes caused by the nine-year-long enemy’s aggression, especially the last year after the large-scale invasion of the country’s territory by russian troops in February 2022. The article aims to detect and examine the features of innovative entrepreneurship’s impact on the socio-economic development of regions and territories as an element of strategic management during the country’s post-war recovery based on the preparation for Ukraine’s accession to the European Union. On the example of strategic planning of the Lvivska Oblast development, the article addresses the conceptual approaches to regional development management from the viewpoint of innovative entrepreneurship as an essential element of economic growth. Major parameters of innovative activity of Lvivska and Ivano-Frankivska oblasts regional level are analyzed. The dynamics and structure of the main funding sources for R&D expenditures and the types of economic activity in Lvivska Oblast that have innovation capacity are examined, including smart specialization, creative industries, and bioeconomy. The problems that restrain innovative processes on national and regional levels and might affect the development of industries with high added value during the country’s recovery and reconstruction in the post-war period and on the way of preparation for Ukraine’s accession to the European Union are outlined. The article emphasizes the lack of efficient communication between science, businesses, and authorities, requiring more thorough analysis and development of tools to improve the mechanisms of interaction in the innovative market. Special attention is paid to the need to improve, measure, and estimate statistical parameters of innovative activity formed by the participants of the innovative process at all management levels.
Keywords: innovative entrepreneurship; strategic management; strategic development; region; innovative process; creative industries